Analysis of production systems of farms in Paracatu, MG, Brazil - Franz, Paulo Renato F. (Pesquisa Agropecuaria Brasileira, 2014)
This work studies the production systems of farms in Paracatu, Mcl, trying to identiíy their limiting factors and the possible impacts of teehnological innovations. It also makes a diagnosis of their natural resources and studies the profitability of these farms based on the "gross margin per ha" (MBIha). To relate MB/ha to various economie indicators a computer program was used (LISA-Logiciel Intégrá des Systèmes Agraires). The farm group analyzed demonstrates heterogcneity. The most modera farms proved to be more profitable, more eostly and more dependent on external factors suei as imputs, machinery and baus. They also are located in flat regions and administered by more educated farmers, that produce grain for trading. Tbe traditional farms are found in lands with irregular terrain. They are managed by older and less cducated farmers, and are dedicated to subsistence íarming, generalby for dairy cattle production. A schcme of differential modernization might be proposed to incorporate the results of technological progress into the production systems of the farmers, higher capitalized farms, and an improved system of subsistence farming compatible with acceptable living standards
Keywords: diagnosis; gross margin